True blood. The complete third season [videorecording (DVD)] - Ball, Alan, 1957-; Paquin, Anna; Moyer, Stephen; Skarsgård, Alexander; Harris, Charlaine (Home Box Office, 2011)
The Maenadian reign of terror may be over, but Sookie Stackhouse and the townspeople of Bon Temps face a new calamity that makes the bacchanalian evils of Maryanne Forrester seem tame by comparison. Sookie desperately tries to locate her fiance, ending up in a netherworld of human and undead interlopers, among them the powerful Vampire King of Mississippi, Russell Edgington.